An inclusion complex of eugenol into β-cyclodextrin: Preparation, and physicochemical and antifungal characterization. (1st April 2016) - Gong, Liang; Li, Taotao; Chen, Feng; Duan, Xuewu; Yuan, Yunfei; Zhang, Dandan; Jiang, Yueming
Highlights: An inclusion complex encapsulated EG into βCD was prepared by saturated solution method. The βCD–EG inclusion complex was characterized by 1 H NMR, NOESY and SEM. The βCD–EG inclusion complex showed great promising for control of P. litchii in vitro and in vivo . The model of action of the βCD–EG inclusion complex against P. litchii was explored firstly. The βCD–EG inclusion complex could serve as a safe and high-efficiency fungicidal microcapsule. Abstract: The inclusion of eugenol (EG) into β-cyclodextrin (βCD), its structural characterization and antifungal activity, and mode of action for control of Peronophythora litchii in postharvest fresh litchi fruits is described. Nuclear magnetic resonance spectra revealed chemical shifts in H-3 and H-5 protons of βCD, indicating EG inclusion into the lipophilic cavity of βCD. In vitro assays showed βCD–EG significantly inhibited P. litchii colony growth in a concentration- and time-dependent manner (MIC100 = 0.2 g). In vivo assays showed βCD–EG significantly ( p < 0.05) reduced the decay index of treated fresh litchi fruits. After exposure to βCD–EG, the surface of P. litchii hyphae and/or sporangiophores became wrinkled, with folds and breakage observed by scanning electron microscopy. Damage to hyphal and/or sporangiophore cell walls and membrane structures post-treatment with βCD–EG was confirmed by transmission electron microscopy. Therefore, βCD–EG shows great potential as a controlled-release agent against P. litchii .